Descriptive Analysis of Grade VIII Physics Test Scores - Neng Suci Hasnabila; Irma Fitria Amalia; Dini Andriani (Jurnal Pendidikan dan Humaniora, 2026)
This study aims to describe students' mastery of Physics material at the junior high school level through a descriptive analysis of test scores. The research was conducted on 32 grade VIII students of SMPN 1 Sukawening Garut using a descriptive quantitative approach. Data were collected through documentation of student test scores and analyzed using measures of central tendency (mean, median, mode) and score-interval frequency distribution. The results show that the average score was 75.36, the median was 73, and the mode was 62, with scores ranging from 58 to 100. Based on the minimum mastery criterion (KKM) of 75, only 12 of the 32 students (37.5%) passed, while 20 students (62.5%) had not yet reached mastery. The score distribution shows that most students are concentrated in the moderate-to-high interval (70-100), although a considerable number remain in the moderate-low interval (60-69). These findings indicate an uneven mastery of physics concepts among students, highlighting the need for remedial programs for students below the standard and enrichment activities for high-achieving students.